2007
DOI: 10.1021/ie070457i
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Power Spectrum of Acoustic Emission (AE) by Accelerometers in Fluidized Beds

Abstract: Power spectrums of acoustic emission (AE) on the walls of fluidized beds were calculated, to investigate the particle movement in the bed. It is determined that the main frequency of the AE power spectrum can be related to the average Landau−Lifshitz collision time of particles impacting on the walls of the bed. A frequency model was proposed to examine the effect of superficial velocity, the size and density of particles, and the elastic modulus of the materials. The influence of chunk formation on the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 8 publications
1
38
0
Order By: Relevance
“…As stated above, only a few examples can be found in the literature (Jiang et al, 2007;Leach et al, 1978) that provide information to generate some understanding of the carrier frequency band properties characterizing the measured accelerometer signal.…”
Section: Flow-induced Vibration In Fluidized Bedsmentioning
confidence: 99%
See 3 more Smart Citations
“…As stated above, only a few examples can be found in the literature (Jiang et al, 2007;Leach et al, 1978) that provide information to generate some understanding of the carrier frequency band properties characterizing the measured accelerometer signal.…”
Section: Flow-induced Vibration In Fluidized Bedsmentioning
confidence: 99%
“…A model developed in (Jiang et al, 2007) based on the relationship between particle collisions and acoustic signals dealt with the measurement of the elastic waves produced by the particle-particle and particle-wall collisions. Consequently, the expected carrying resonant frequency band had considerably high frequency values, requiring the use of very high sampling frequencies ranging from 100 kHz to 500 kHz (Jiang et al, 2007;Tsujimoto et al, 2000). Even though several reports suggested that these high frequency methods can be tuned to serve for some fluidized bed applications, the sampling frequencies on the order of hundreds of kHz considerably can increase the computational costs needed to handle the monitoring problem.…”
Section: Flow-induced Vibration In Fluidized Bedsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, AE signal is sensitive and selective to the movement of the particles. Many recent publications on the applications [19][20][21][22][23][24][25][26] of AE measurement indicate that they lead to reliable quantitative results and do not function just as qualitative indicators, as was the case in the beginning phases of AE-based applications in nondestructive testing. 19 In this work, we for the first time developed and applied a passive acoustic emission (AE) technique, to investigate the flow regime and fluidization condition of polyethylene particles in a gas-solid fluidized bed.…”
Section: Introductionmentioning
confidence: 99%